Dysregulated glucose metabolism in the visual cortex of human subjects with mild cognitive impairment and Alzheimer's disease. - Mjaaseth, Ulrik N.; Hsu, Ming-Fo; Arballo, Joseph; Haj, Fawaz G.; Patel, Viharkumar (Frontiers in Aging Neuroscience, 2026)
Introduction: Alzheimer's disease (AD) is characterized by progressive neurodegeneration and impaired glucose metabolism. While most studies focus on heavily affected brain regions such as the hippocampus and prefrontal cortex, the visual cortex remains relatively preserved in early AD and provides an opportunity to examine metabolic alterations that precede widespread pathology. Methods: Postmortem human visual cortex samples were obtained from control, mild cognitive impairment (MCI), and AD subjects without non-AD neuropathologic conditions. Untargeted metabolomics was performed using liquid chromatography–mass spectrometry, and expression of key metabolic, inflammatory, and AD-related genes was measured by quantitative PCR. Data analysis was conducted using MetaboAnalyst and R. Results: Metabolomic profiling revealed progressive disruptions in glucose metabolism, and mitochondrial function across MCI and AD subjects. Gene expression analyses showed reduced levels of glycolytic enzymes (HK1 , PFKM , PKM1), mitochondrial regulators (PDHA1 , NDUFC1), and the neuronal glucose transporter SLC2A3. Insulin signaling was altered, with decreased IDE and increased INSR and PTPN1 gene expression. Inflammatory markers including TNF , IL1B , and GFAP were elevated in AD. Sex-stratified analyses revealed both shared and distinct metabolic signatures, particularly within glucose and mitochondrial pathways. Several metabolic gene changes correlated negatively with Braak stage, highlighting a progressive decline in energy metabolism alongside tau pathology. Discussion: These findings demonstrate early and progressive metabolic dysfunction in the visual cortex of MCI and AD subjects. Even in a region with limited structural pathology, profound alterations in energy metabolism were observed, underscoring its central role in AD pathogenesis and highlighting improving neuronal metabolic function as a promising target for therapeutic intervention.